Implementasi Nilai Moderasi Beragama Pada Anak Berkebutuhan Khusus - Ni Wayan Ria Lestari (Jayapangus Press, 2023)
Education is basically an effort to improve one's self-quality. Education is not only obtained at school, but also in the family and community. Schools as a forum for education in Indonesia and as a formal institution in the world of education have an important role in the growth and development of a child. For example, Special Schools which are part of formal education institutions have been provided by the government as a place to carry out education for special children. The goal is to give hope to them so that they no longer get discriminatory treatment from the surrounding environment. The type of data in this study is qualitative descriptive. In this study, researchers obtained data through several ways, including: from observation, documentation, and through interviews. The results include: Religious moderation learning strategies for students with special needs are tailored to the level of needs of their students. Learning religious moderation can be done by lecture methods in the classroom and direct practice (learning outside the classroom). The implications of religious moderation learning for students with special needs are reflected in students' daily activities, including habitually greeting every time they meet teachers and elders. Obstacles or obstacles in implementing religious moderation learning for children with special can be sourced from internal students can also be from external such as students lack focus in learning in class, students' ability to write and read is still lacking and students still often play and chat with their friends.